A MODEL OF PHANEROZOIC CYCLES OF CARBON AND CALCIUM IN THE GLOBAL OCEAN: EVALUATION AND CONSTRAINTS ON OCEAN CHEMISTRY AND INPUT FLUXES - Locklair R.E.; Lerman A. (My University, 2005)
The relationships between the global carbon cycle and paleo-climates on short and long time scales have been based on studies of accumulation rate of the two main components of the sedimentary carbon reservoir, organic carbon and carbonate carbon. Variations in the rate and proportion of carbonate burial through Phanerozoic time have been attributed to the effects of tectonics on eustasy, atmospheric CO2 concentration, MOR (Mid-Ocean Ridge) hydrothermal flux, and weathering and riverine flux. This study addresses the history of variations in the state of the surface ocean and its degree of saturation with respect to calcite and aragonite, based on a geochemical model that considers the Phanerozoic atmospheric PCO2 and surface ocean temperature reconstructions as the main forcings on the system. The results show that, using near-present-day values of ocean salinity and alkalinity, the Early Paleozoic and Middle Mesozoic oceans are calculated to be undersaturated (or nearly undersaturated) with respect to CaCO3. For the near-present-day values of supersaturation (ω=ICP/Ksp) of 3-5 with respect to calcite, paleo-alkalinity of ocean water would have been up to 2.5 times greater than at present, although the pH values of surface ocean water would have been somewhat lower than the present values. This alkalinity factor is consistent with a higher calcium concentration (up to ×2.5) due to increased circulation at ocean spreading-zones and also higher salinity (up to ×1.5) attributed by other authors to segments of the geologic past. Our model results indicate that although PCO2 was a contributing factor to shifts between calcite and aragonite saturation of seawater, additional changes in alkalinity were needed to maintain supersaturation at the level of 3-5, comparable to the present. Continental weathering of crystalline and older carbonate rocks, in addition to MOR (Mid-Ocean Ridge) circulation, was likely an important mechanism for maintaining supersaturation of surface ocean water, particularly during times of increased carbonate storage. © 2005 Elsevier B.V. All rights reserved.
Keywords: ALKALINITY; CALCIUM CARBONATE; CARBON CYCLE; CARBONATE MINERALS SATURATION; PHANEROZOIC; Mesozoic; Paleozoic